Financial capture theory and its impact on improving profitability indicators in commercial banks - حمزة محمود الزبيدي; سعدي احمد حميد (Iraqi Journal for Administrative Sciences, 2025)
The study addressed the issue of financial capture and its impact on improving profitability indicators in commercial banks. Two very important variables in financial thought were studied, the first of which was the formulation of the capital structure in business establishments according to the capture theory, and the second was profitability indicators, which are linked to achieving the strategic objectives of the establishments. The study chose commercial banks. listed on the Iraq Stock Exchange as a field for applying the study, as (4) four commercial banks were chosen from among them, and the study planned a time series consisting of five years (2007, 2008, 2009, 2010, 2011), and the problem of the study was embodied in the intellectual debates and problems between Researchers and thinkers are examining the level of maturity of knowledge in how to differentiate between owned and borrowed sources of financing to build and formulate a capital structure that helps commercial banks in particular and businesses in general in achieving their strategic goals. Among the most prominent results and conclusions reached by the study is proving the validity of the hypotheses that were formulated and proving the existence of correlations and impact. He demonstrated the formulation of capital structure according to the capture theory and profitability indicators, which concluded that profitability indicators increase in commercial banks as a result of applying the capture theory philosophy. The most prominent recommendations that came out of the study are the recommendation of the necessity of monitoring the state of formulating the capital structure in commercial banks because of its great importance in influencing the levels of profitability and thus influencing the levels of achieving the strategic objectives of those banks. The study also recommended the necessity of adopting the philosophy and ideas of capture theory in formulating The capital structure in commercial banks because it is compatible with the Iraqi business environment, especially the banking business environment in Iraq.